Evidence for health : from patient choice to global policy - Andermann, Anne, 1972- (Cambridge University Press, 2013)
"Evidence for Health: From Patient Choice to Global Policy is a practical guide to evidence-informed decision-making. It provides health practitioners and policy-makers with a broad overview of how to improve health and reduce health inequities, as well as the tools needed to make informed decisions that will have a positive influence on health. Chapters address questions such as: What are the major threats to health? What are the causes of poor health? What works to improve health? How do we know that it works? What are the barriers to implementation? What are the measures of success? The book provides an algorithm for arriving at evidence-informed decisions that take into consideration the multiple contextual factors and value judgements involved. Written by a specialist in public health with a wealth of international experience, this user-friendly guide demystifies the decision-making process, from personal decisions made by individual patients to global policy decisions"--Provided by publisher.